2006
DOI: 10.1163/156856206778366059
|View full text |Cite
|
Sign up to set email alerts
|

Blood cell and plasma protein repellent properties of Star-PEG-modified surfaces

Abstract: The implantation of biomaterials, medical devices or prostheses can instigate a rejection response or initiate an undesirable adsorption of plasma proteins, as well as blood cells on the implant surface, thus triggering diverse defense mechanisms against the supposed pathologic invader. The extent of this inflammatory reaction depends in part on the biocompatibility of the used materials or coatings. Although adsorption and coagulation responses can appear during the total in vivo lifetime of the implant, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 18 publications
4
38
0
Order By: Relevance
“…By testing three different types of polymeric particles (PLA, PNIPAM-NH 2 and PEG) with different biocompatibilities [60, 61], our studies show that there is a very good linear relationship between chemiluminescence intensities and histological inflammatory measurements. As expected, the stronger inflammatory reactions are accompanied with higher L-012-dependent chemiluminescence intensities.…”
Section: Discussionmentioning
confidence: 99%
“…By testing three different types of polymeric particles (PLA, PNIPAM-NH 2 and PEG) with different biocompatibilities [60, 61], our studies show that there is a very good linear relationship between chemiluminescence intensities and histological inflammatory measurements. As expected, the stronger inflammatory reactions are accompanied with higher L-012-dependent chemiluminescence intensities.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different ways in which these polymers can be attached to the surface. Also the sort of polymers used can differ from linear to branched, like star-shaped, and from homo-polymers to block-copolymers [34][35][36][37]. These polymers all have in common that they are in most cases hydrophilic.…”
Section: Protein-and Microorganism-repellent Coatingsmentioning
confidence: 99%
“…Due to the soft consistency of liver parenchyma in some cases, liver tissue protruded through the gaps between the mesh filaments. Previous in vitro studies on cell cultures using the same type of chemical substances described here suggested cell-repellent and anti-adhesive qualities [10,20,21]. This certainly was not demonstrable within this in vivo animal model.…”
Section: Discussionmentioning
confidence: 59%